Methods of Measuring and Simulating the Intracluster Light of Galaxy Clusters - de-Ville, Jordan (2024)
This thesis examines the Intracluster Light (ICL) of galaxy clusters, using both simulated and real observations. We, first, used data from the Millennium MAMBO lightcone to devise a method of simulating realistic images of the ICL for a given cluster. These simulated images may be used to infer the limiting capabilities of ICL detection codes, and to test whether reduction pipelines are suitable for ICL studies. They also allow users to further optimise their codes, as the input ICL variables are known.